(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يعنى هذا البحث بعرض منهجية متكاملة لحساب الخصائص الترموديناميكية الحرارية للبلورات على امتداد المنحنيات الإيزوحرارية الموافقة لكل درجات الحرارة بما في ذلك المساوية لدرجة حرارة انصهار البلورة فأعلى عند قيم مختلفة لحجمها المولي تصل حتى قيمته الموافقة لمنحنيات التوازن التجريبية مع الطورين الغازي والسائل وضمن حدود تطبيق التقريب شبه التقليدي. و تقوم هذه المنهجية على أخذ قوى التأثير المتبادل الثنائية و قوى التأثير المتبادل الثلاثية بعين الاعتبار. وبغية التأكد من فعالية المنهجية المقترحة طبقت على بلورة الأرغون عند درجة الحرارة 60 درجة كلفن حيث تتوفر المعطيات التجريبية وقورنت بالنتائج التجريبية لباحثين آخرين. تشير المقارنة بوضوح إلى توافق النتائج المحسوبة مع النتائج التجريبية. This work suggests a methodology for calculating the thermal thermodynamic properties of crystals along isothermal curves, expanded from any temperature through melting point temperature and up at different molar volume values expanded up to its value, corresponding experimental equilibrium curves with gaseous and liquid phases within the framework of quasi-classical approximation. The pair-wise inter-atomic forces in conjunction with three-body forces were taken into consideration in methodology. In order to ascertain the effectiveness of the proposed methodology it was applied for calculating the thermal properties of crystalline Argon at 60K temperature where experimental data are available. The calculated results were compared with available experimental data. The comparison clearly indicates that the calculated results coincide well with the experimental results.